Peradilan Agama sebelum Masuknya Islam di Indonesia - Jauhari, Muhammad Robah (Maliki Interdisciplinary Journal, 2025)
The history of Religious Courts in Indonesia before the arrival of Islam, during the sultanate, and during the Dutch colonial period. Before the arrival of Islam, the Indonesian judicial system already had two types: Civil Courts and Co-Courts. Civil Courts dealt with royal matters and were derived from Hindu law, while Co-Courts dealt with matters outside the royal sphere and were guided by indigenous Indonesian law. When Islam arrived in Indonesia around the 7th century AD, Islamic law began to develop and coexist with customary law. In the early period, dispute resolution was carried out through tahkim, where disputing parties submitted their case to a religious expert and agreed to abide by his decision. With the formation of Islamic kingdoms, judges were appointed by the sultan or imam, marking the period of tauliyah (leadership) of the imam. This section also describes the development of Religious Courts in various regions, both in Java (Cirebon, Banten, Surakarta, and Yogyakarta) and outside Java. In Banten, the judiciary was based on Islamic law, while in Cirebon, Old Javanese law was used. The authority of the Religious Courts in Surakarta and Yogyakarta became limited after various regulations by the Dutch East Indies government, such as Staatsblad No. 30 of 1847. Developments outside Java also varied, influenced by different colonial policies in each region, such as in Palembang, Jambi, and Bengkulu, where Religious Courts still have a role even though they are not always officially recognized in all places. This paper emphasizes that the judicial system in Indonesia continues to develop and has a complex and long history, especially since the sultanate era.